Laccase and glucono-δ-lactone dual-induced gelation of casein and arabinoxylan: Microstructures, physicochemical properties, and pH-responsive release behavior. (February 2023) - Liu, Wenwen; Zhu, Lin; Liu, Yongjia; Xie, Zhuohong; Yang, Puyu; Zhang, Yaqiong; Gao, Boyan; Yu, Liangli (Lucy)
Abstract: In this study, dual-induced casein and arabinoxylan composite gels (casein/AX gels) were successfully prepared by laccase and glucono-δ-lactone (GDL). The influence of AX amount on the microstructure and properties of casein/AX gels was also evaluated. Compared to that of the single casein gel, the rheological and textural properties of casein/AX gels were improved, which might be attributed to the co-existence of covalent and non-covalent interactions of AX and casein molecules, resulting in the interconnected network gel microstructure observed by scanning electron microscopy (SEM). Besides, with the increased amount of AX, casein/AX gels showed an increased water holding capacity and a decreased water mobility significantly ( P  < 0.05). Meanwhile, epigallocatechin gallate (EGCG) was loaded into casein/AX gels more efficiently and released in a pH-responsive pattern. Only 10–22% of the loaded EGCG was released from casein/AX gels in the simulated gastric fluid (SGF). In contrast, most EGCG was released in the simulated intestinal fluid (SIF), showing great potential to protect EGCG from degradation at low pH conditions. Graphical abstract: Image 1 Highlights: Dual-induced casein/arabinoxylan gel was prepared by laccase and glucono-δ-lactone. Covalent and non-covalent interactions co-existed in casein/arabinoxylan gels. The microstructure and properties of gels were influenced by arabinoxylan amount. Casein/arabinoxylan gels had higher loading efficiency and pH-responsive behavior.